Implementation of Universal Design Concept on Lecture Space for Students with Hearing Disabilities - Harahap, Rachmita Maun; Santosa, Imam; Wahjudi, Deddy; Martokusumo, Widjaja (The Center for Disability Studies and Services Brawijaya University, 2019)
Campus building is where students undergo of learning process and perform various activities. In learning process, campus should provide universal design facilities for students all, including students with disabilities. The design of campus is important factor in operation and service of a higher education. Universal design concept on lecture space in CADL ITB building can make it easier of activity for students with hearing disabilities. The purpose of this research is test a universal design strategy for reducing hearing impairment, visual communication barriers and assistive technology strengthen, but universal design concept to hearing disabilities that is much different and usually involves visual signs.This research uses 3 stages of method that is descriptive qualitative, classification analysis, and proposal design solution method. Using the parameters of universal design principles, factors involved in application can be classified to determine the problem of lecture space in CADL ITB as a case study. Then observation of interview result through questionnaire of 60 respondents of students/alumni/drop out of hearing disability in various universities stated that it is still difficult to be accessed in lecture space because there is no universal design facility available. While informants 10 persons academic and not academic people understand and universal design knowledge for disabled except hearing disability. Research results of this study indicate that universal design concept on lecture space in CADL ITB building not optimal, then existing problems will be given a design solution to maximize of universal design concept.